Sobre o encontro de Panstrongylus megistus no município de Cambé, Estado de Paraná, Brasil On the occurrence of Panstrongylus megistus in the county of Cambé, State of Paraná, Brazil - Almério de Castro Gomes; Ivete Shimada (Universidade de São Paulo, 1976)
Relata-se o encontro de Panstrongylus megistus no sítio Shimada, localizado no município de Cambé, Estado do Paraná. Caracteriza-se ecologicamente a área e aborda-se possíveis fatores humanos implicados na ocorrência deste triatomíneo, em um domicílio. The report describes the occurrence of Panstrongylus megistus on the Shimada farm, located in Cambé, State of Paraná. The área is characterised ecologically and possible human factors related to the occurrence of this Triatominae in one dwelling are pointedout.